Hyperphosphatasemia in leiomyosarcoma of the uterus: Two case reports and a literature review. Issue 9 (10th July 2017) - Jitsumori, Mariko; Umeda, Anna; Hosoi, Ayako; Miyanishi, Kazuya; Munakata, Satoru; Yamamoto, Toshiya
Abstract: Some tumors are known to produce alkaline phosphatase (ALP). Seven cases of uterine leiomyosarcoma were identified from the clinical records of Sakai City Medical Center from January 2006 to December 2014. Patients' ages ranged from 47 to 75 years (median: 58). Clinical stages were IB, IIB, IIIA, and IVB in four, one, one, and one cases, respectively. Of these, two were found to have hyperphosphatasemia before surgery, and the elevated ALP level decreased after surgery, and increased with disease recurrence. In the cases of hyperphosphatasemia, leiomyosarcoma cells showed positive staining for ALP. There was no correlation between serum ALP and lactate dehydrogenase, or ALP and cancer antigen 125. The combination of ALP, lactate dehydrogenase, and cancer antigen 125 may be more useful for diagnosis and follow‐up of leiomyosarcoma.